Frontier molecular orbital, molecular structure and Thermal properties of 2, 4, 6, 8-tetramethyl-2, 3, 6, 7-tetrahydro-s-indacene-1, 5-dione using DFT calculation. (2022) - Sucheta, M.; Pramod, A.G.; Zikriya, Mohamed; Mohammed Salma, K.; Venugopal, N.; Chaithra, R.; Harshitha, D.; Amudan, S.; Renuka, C.G.; Murthy, Shiva
Highlights: The DFT theory with DFTB3LYP6311++G(dp_basis set is used to calculate the theoretical calculations. The HOMO and LUMO energy values are found to be −6.649 and −2.259 eV respectively. The bandgap energy of the molecule is found to 4.38 eV (wide bandgap value). The molecule studied can be used for optoelectronic applications. The total energy of the molecule is found to be −770.829258 Hatree. Abstract: The quantum chemical calculations of 2, 4, 6, 8-tetramethyl-2, 3, 6, 7-tetrahydro-s-indacene-1, 5-dione molecule were carried out with DFT calculations using DFTB3LYP/6–311++G(d, p) basis set by Gaussian 09 W code. The molecular structure, frontier molecular orbitals (HOMO, LUMO), and thermal properties were explained in this article. From the molecular structural result, we found that the titled molecule more active at O-13 and O-14 oxygen atom. From the frontier molecular orbital study, the HOMO molecular orbital energy is found to be −6.6496 eV and the LUMO molecular orbital energy is found to be −2.2599 eV. The electro negativity and electro positivity and electron density of the titled molecule was calculated from the molecular electrostatic potential maps. The stability, chemical hardness, global softness, and elecrtrophilicity index were also estimated.